Mechanistic studies on the CAN-mediated intramolecular cyclization of δ-aryl-β-dicarbonyl compounds - Casey, Brian M.; Sadasivam, Dhandapani V.; Flowers II, Robert A. (Beilstein Journal of Organic Chemistry, 2013)
The synthesis of 2-tetralones through the cyclization of δ-aryl-β-dicarbonyl substrates by using CAN is described. Appropriately functionalized aromatic substrates undergo intramolecular cyclizations generating 2-tetralone derivatives in moderate to good yields. DFT computational studies indicate that successful formation of 2-tetralones from δ-aryl-β-dicarbonyl radicals is dependent on the stability of the subsequent cyclohexadienyl radical intermediates. Furthermore, DFT computational studies were used to rationalize the observed site selectivity in the 2-tetralone products.
Keywords: CAN oxidation; β-dicarbonyls; free radical; radical arylations; tetralones